Accomplishment of goal levels in multi team systems: Role of leadership skills and multicultural teams - Nawaz, Muhammad; Tahir, Asma; Khan, Rana Mumtaz; Bhatti, Ghulam Abbas; Namatullah, Alina (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
Teams are increasingly engaged in networked interaction across teams and organizational boundaries in order to achieve complex, lower order and higher order goals. Considering the fact that the goals accomplishment is the basic necessity of organizations, this study aims at exploring the accomplishment of goal levels in multi team systems (MTSs). There exists an absence of theoretical models focused on systems composed of such teams. This study therefore, proposes a predictive model to improve understanding in this regard. It has been suggested that the higher order goals are more effective to accomplish under sequential and reciprocal functional process inter dependencies. Conversely, the lower order goals are more effective to accomplish under intensive functional process inter dependency. However, this goal achievement requires facilitators to make it more effective because of which moderators such as leadership skills and multicultural teams are proposed within the suggested framework.